Blended Learning: Can It Be a Solution to Improve Digital Literacy and HOTS for PGSD Students in a Pandemic Situation? - Dewi, Ririn Andriani Kumala; Fatkhiyani, Kiki (International Journal of Elementary Education, 2021)
The Covid-19 pandemic in the industrial revolution 4.0 era transformed traditional learning into online-based learning with the implementation of distance learning (PJJ). However, in its implementation, it still encounters several obstacles, such as the lack of digital literacy skills. One of the solutions offered is blended learning which combines traditional learning with online learning in order to complement the shortcomings of each learning method. The purpose of this study is to prove whether there is an effect of blended learning on increasing digital literacy and HOTS of PGSD students. The methodology used is experimental research with Pre-Experimental Design with One-Group Pretest-Posttest Design model. The sample in this study was 55 PGSD students. The instruments used are digital literacy questionnaire sheets and HOTS test sheets. The results of the paired sample t-test for the effect of blended learning on digital literacy resulted in the value of sig. (2-tailed) of 0.000 is smaller than which is 0.05. This means that blended learning has an effect on students' digital literacy skills. The results of the n-gain test for increasing digital literacy after applying blended learning obtained an n-gain of 0.56 in the medium category and the n-gain of students' HOTS results of 0.55 also in the medium category, so it can be concluded that there is an effect of blended learning on increasing literacy. digital and student HOTS.